2021
DOI: 10.1177/00031348211011063
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Costs and Outcomes of Open, Laparoscopic, and Robotic Liver Resections

Abstract: Introduction Most liver resections performed in the United States are open. With the ever-increasing role of robotic surgery, our study's role is to assess national outcomes based on the surgical approach. Methods We performed a retrospective analysis of the 2015 National Readmission Database (NRD). We selected patients undergoing open, laparoscopic, and robotic hepatectomy. Propensity score matching was performed to match the three groups in terms of demographics, hospital characteristics, and resection type.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Due to the inherent nature of this study, information bias and its effect on the outcomes cannot be excluded. One of the most frequently debated disadvantages of robotic surgery is the increased cost though a recent study has shown that RLR is cost‐effective 29 . As this study was multicentric, data needed for comparison of cost between the two modalities was not available and hence cost analyses could not be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the inherent nature of this study, information bias and its effect on the outcomes cannot be excluded. One of the most frequently debated disadvantages of robotic surgery is the increased cost though a recent study has shown that RLR is cost‐effective 29 . As this study was multicentric, data needed for comparison of cost between the two modalities was not available and hence cost analyses could not be performed.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most frequently debated disadvantages of robotic surgery is the increased cost though a recent study has shown that RLR is cost-effective. 29 As this study was multicentric, data needed for comparison of cost between the two modalities was not available and hence cost analyses could not be performed. Heterogeneity in clinical practice amongst the centers with regards to patient selection, surgical approach and techniques, and surgeon/center experience may also prove to be confounding variables in interpreting the results of this study.…”
Section: T a B L E 1 (Continued)mentioning
confidence: 99%
“…[65] However, a recent study reported that robotic liver surgery was associated with lower total costs when including cost per readmission versus its open and laparoscopic counterparts. [81] Notably, most published studies have not accounted for the considerable capital and maintenance costs of the robotic system. [75] Nevertheless, the value-outcomes plus patient experience divided by economic cost-of PLLDH/RLDH versus OLDH needs to be better understood.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first comparative reports of major RLDH versus OLDH showed higher total costs for RLDH 65 . However, a recent study reported that robotic liver surgery was associated with lower total costs when including cost per readmission versus its open and laparoscopic counterparts 81 . Notably, most published studies have not accounted for the considerable capital and maintenance costs of the robotic system 75 …”
Section: Discussionmentioning
confidence: 99%
“…The higher costs were mostly associated with length of stay and operating room time. Another study conducted a retrospective analysis of data from the 2015 National Readmission Database in the United States [ 69 ]. Three groups were evaluated using propensity-matched analysis of open, laparoscopic, and robot-assisted resections.…”
Section: Robot-assisted Hepatic Surgerymentioning
confidence: 99%